2016
DOI: 10.3390/e18030084
|View full text |Cite
|
Sign up to set email alerts
|

Entropy and Fractal Antennas

Abstract: Abstract:The entropies of Shannon, Rényi and Kolmogorov are analyzed and compared together with their main properties. The entropy of some particular antennas with a pre-fractal shape, also called fractal antennas, is studied. In particular, their entropy is linked with the fractal geometrical shape and the physical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(111 citation statements)
references
References 38 publications
1
110
0
Order By: Relevance
“…This fact may confirm, from a mathematical point of view, the idea from statistical fractal mechanics [5][6][7][8][9], according to which the complex probability density must be, also, a movement integral. Since our Lie's group in the space of null vectors is isomorphic to the Barbilian group (for details, see [17]), it results that the complex Gaussian Equation (33), with additional constrains [21], can have the role of an entropy in a fractal theory of motion [12].…”
Section: Fractal Entropy Through Non-differentiable Lie's Groupsupporting
confidence: 65%
See 1 more Smart Citation
“…This fact may confirm, from a mathematical point of view, the idea from statistical fractal mechanics [5][6][7][8][9], according to which the complex probability density must be, also, a movement integral. Since our Lie's group in the space of null vectors is isomorphic to the Barbilian group (for details, see [17]), it results that the complex Gaussian Equation (33), with additional constrains [21], can have the role of an entropy in a fractal theory of motion [12].…”
Section: Fractal Entropy Through Non-differentiable Lie's Groupsupporting
confidence: 65%
“…[6][7][8][9]. Moreover, the analysis of complex systems evolution showed that most of them are non-linear and, therefore, new mathematical tools were required.…”
Section: Introductionmentioning
confidence: 99%
“…In order to define a diversity order, we borrow the definition of Renyi entropy, which is widely used to define a diversity order in biology and many other fields [17][18][19][20][21][22]. Renyi entropy is written as:…”
Section: New Definition Of Diversity Ordermentioning
confidence: 99%
“…OFDM has also been adopted by numerous wireless transmission standards such as long term evolution (LTE) and wireless local area network (WLAN) [5,6], which adopt the multiple-input multiple-output (MIMO) technique as the key technology to cope with increasing transmission reliability without any additional wireless bandwidth. There has been explosive adoption of MIMO technology in the wireless environment to improve the performance of antennas and transceivers [7][8][9].…”
Section: Introductionmentioning
confidence: 99%